An Analysis of Knowledge and Attitude of Alumnus of STIKes Santa Elisabeth Medan on Applying English in Domestic and in Abroad - Amando Sinaga; Rusmauli Lumbangaol (Sean Institute, 2023)
English as foreign language considered very essential to deliver and to access information, to observe knowledge, technology, art and guiding relationship with other nations. The purpose of this study is to analyze the alumnus attitude and knowledge in applying English. The study uses qualitative method by collecting the data of action research namely explaining the knowledge and attitude. In overseas, particularly in Japan, the using of English pronunciation, vocabularies and grammar are not frequently because the English using is rare in daily communication. The respondents use local language and even they hardly ever use English. Through this reasons, English lessons; grammar, pronunciation, vocabularies they ever studied are forgotten. But, it is also found that sometimes when English native patient come, they have to serve to do checking vital signs and so on but it is difficult for them because English is rarely used. But not for alumni who are working in German. It is found that there is a progress of knowledge and attitude. German is one of European country and English is largely used by people. So, the applying English is almost every day. Domestically, the alumni knowledge and attitude are stagnant. It is not seen that there is no significant change of progress or decline. This finding is based on the alumni’s ability to answer the question proposed. But, there are no significant progress. It can be concluded that the alumni’s knowledge and attitude is determined by how often they use English.